1995
DOI: 10.1507/endocrj.42.95
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Inhibin .ALPHA., and .BETA.A Subunit and Activin Type II Receptor mRNAs in Various Human Pituitary Adenomas.

Abstract: Abstract. Inhibin and activin are known to be involved in the pituitary hormone secretion as well as proliferation of the pituitary. We studied the expression of inhibin a, and 13A subunit and activin type II receptor (ACTR 2) mRNAs in human pituitary adenomas to determine the significance of inhibin and activin in pituitary hormone secretion. Tumor tissues were homogenized immediately after resection in guanidinium thiocyanate to extract total RNA. PCR was performed with reversely transcripted cDNA and respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
7
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
3
7
0
Order By: Relevance
“…In addition, activin has been reported to affect GH [3,4] and FSH [5] secretion from human pituitary adenomas. Along with these observations, several studies [6][7][8] including ours demonstrated the inhibin a subunit [6,8], 13 subunit [7,8] and activin type 2 receptor (ACTR 2) mRNAs expressions [8] in some human pituitary adenomas. All of these findings extended those found in rats [9][10][11][12] 32P labeled antisense primers made by the 5'end labeling methods.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…In addition, activin has been reported to affect GH [3,4] and FSH [5] secretion from human pituitary adenomas. Along with these observations, several studies [6][7][8] including ours demonstrated the inhibin a subunit [6,8], 13 subunit [7,8] and activin type 2 receptor (ACTR 2) mRNAs expressions [8] in some human pituitary adenomas. All of these findings extended those found in rats [9][10][11][12] 32P labeled antisense primers made by the 5'end labeling methods.…”
supporting
confidence: 70%
“…The oligonucleotide primers and the amplification protocols for each PCR were the same as described previously [8]. Briefly, cDNA generated by reverse transcription from total RNA was amplified for inhibin a and /3A subunits as follows: samples or standard templates obtained from respective PCR products were incubated with specific sense and antisense primers, deoxynucleosidetriphosphates (Pharmacia Biotech Co., Tokyo), AmpliTaq DNA polymerase (Takarashuzou Co., Ohtsu, Japan), PCR buffer (Takarashuzou Co., Ohtsu, Japan), and Quantitative PCR standard curves for a and 1'A subunit mRNAs are shown in Fig.…”
Section: Quantitative Rt-pcr Resultsmentioning
confidence: 99%
“…Coexpression of inhibin a, /3A and ACTR II mRNAs has been reported in human pituitary adenomas [16], Leydig cell tumor cell lines [17] and teratoma cell lines [18]. All of these reports showed that the tumor tissues may have sites for the action of activin and suggested an autocrine or paracrine role of activin.…”
Section: Discussionmentioning
confidence: 99%
“…Activin type II receptor (ACTR II) was recently cloned and shown to code for proteins comprising intracellular kinase domains with a predicted serine/threonine specificity [15]. Our previous study demonstrated the coexistence of inhibin a and 13A subunit and ACTR II mRNAs in various human pituitary adenomas, particularly gonadotropinomas [16]. Coexpression of mRNAs for the inhibin and activin subunits and ACTR II has also been reported in Leydig cell tumors [17] and a human teratocarcinoma cell line [18].…”
mentioning
confidence: 99%
“…These proteins were not identified in the control study with non-immune serum or preabsorbed antiserum (data not shown). There is accumulating evidence that activin is produced in the pituitary and acts as a local regulator for FSH secretion [6,8,[17][18][19]. The follistatin gene is also expressed in various extragonadal tissues including the pituitary and almost invariably coexists with the activin subunit gene [6,7,20], suggesting that follistatin plays an important role in modulating activin action within these tissues.…”
Section: Molecular Heterogeneity Of Follistatin In the Culture Mediummentioning
confidence: 99%